2019
DOI: 10.1124/mol.119.116269
|View full text |Cite
|
Sign up to set email alerts
|

TRESK (K2P18.1) Background Potassium Channel Is Activated by Novel-Type Protein Kinase C via Dephosphorylation

Abstract: TRESK (K2P18.1) background K 1 channel is a major determinant of the excitability of primary sensory neurons. It has been reported that human TRESK is activated by the protein kinase C (PKC) activator PMA (phorbol 12-myristate 13-acetate) in Xenopus oocytes. In the present study, we investigated the mechanism of this PKC-dependent TRESK regulation. We show that TRESK is activated by coexpression of the novel-type PKC isoforms h and «. The effect of PKC is not mediated by calcineurin phosphatase, which is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…TRESK channels are expressed in a number of neuronal populations in different regions of the central and peripheral nervous systems in addition to the spinal cord and dorsal root ganglia [16,17,19] and can be regulated by Gαq-signaling pathways [4,8,20]. This strongly suggests that TRESK may contribute broadly to the maintenance and regulation of the resting membrane potential in these cell types; channel dysfunction during development of the CNS may therefore also need to be considered because K + -dependent alterations of neuronal membrane potential and excitability are known to cause serious neurodevelopment disorders with intellectual disability (9).…”
Section: Discussionmentioning
confidence: 99%
“…TRESK channels are expressed in a number of neuronal populations in different regions of the central and peripheral nervous systems in addition to the spinal cord and dorsal root ganglia [16,17,19] and can be regulated by Gαq-signaling pathways [4,8,20]. This strongly suggests that TRESK may contribute broadly to the maintenance and regulation of the resting membrane potential in these cell types; channel dysfunction during development of the CNS may therefore also need to be considered because K + -dependent alterations of neuronal membrane potential and excitability are known to cause serious neurodevelopment disorders with intellectual disability (9).…”
Section: Discussionmentioning
confidence: 99%
“…To uncover the relevant channels responsible for the effects of sustained depolarization, we performed experiments in the presence of genistein (non-specific K + channel blocker) that is able to block some K2P channels other than TRESK (Gierten et al, 2008;Zhao et al, 2008), or PMA (protein kinase C [PKC] activator) that blocks TREK-1 and TREK-2 (Enyedi and Czirjá k, 2010) and modestly inhibits TASK channels (Mathie, 2007). Although PMA activates human TRESK, it has little effect on mouse TRESK (Pergel et al, 2019). We found that both genistein and PMA failed to block depolarization-induced suppression of GABAergic responses (Figures S2A-S2D), suggesting that TRESK is a putative channel candidate.…”
Section: Tresk Contributes To Both Sustained Depolarizationinduced Suppression Of Neuronal Efficacy and Shunting Inhibitionmentioning
confidence: 99%
“…In any case, the effect was independent of direct PKC-mediated phosphorilation of the channel since mutation of putative PKC phosphorilation sites did not abolish the PMA effect [ 53 ]. Confirmation of this effect was later reported and the likely mechanism of action involves the nPKC-dependent inhibition of the kinase responsible for the rephosphorylation of the channel at S264 [ 54 ].…”
Section: Involvement Of Tresk In Painmentioning
confidence: 60%
“…In any case, the effect was independent of direct PKC-mediated phosphorilation of the channel since mutation of putative PKC phosphorilation sites did not abolish the PMA effect [53]. Confirmation of this effect was later reported and the likely mechanism of action involves the nPKC-dependent inhibition of the kinase responsible for the rephosphorylation of the channel at S264 [54]. It has been proposed that calcineurin-inhibitor pain syndrome (CIPS) that occurs as a result of the phosphatase activity inhibition by immunosuppressive drugs, such as tacrolimus (FK506) or cyclosporin A, could be due to impaired modulation of TRESK current.…”
Section: Calcineurin Modulation Of Tresk and Pain Sensitivitymentioning
confidence: 82%